Stylistic use of pronouns in scientific medical prose - Капустіна, В. І. (Запорізький державний медичний університет, 2021)
To explore the stylistic use of pronouns and assess those stylistic techniques which help pronouns to achieve some expressiveness in scientific medical prose.